A chlorophyll halo over maud rise in the southern ocean - Ducrocq, Bertrand; Steiger, Nadine; du Plessis, Marcel; Sallée, Jean-Baptiste; Moreau, Sébastien; Swart, Sebastiaan (Nature communications, 2025)
Phytoplankton blooms above the seamount Maud Rise in the Antarctic Ocean have been reported but their emerging mechanisms and their importance for the wider Southern Ocean are not well known. We use satellite data spanning over the last two  decades and in-situ data collected from a ship, an underwater glider and Biogeochemical-Argo profiling floats to understand the processes involved in the formation of Maud Rise phytoplankton blooms. We find that the seamount generates upwelling of warm deep water that transports heat, and likely dissolved iron, to the surface via diapycnal mixing. This creates a recurring annular structure of chlorophyll concentration (or chlorophyll halo) in correspondence with the previously observed warm water and sea ice halo over Maud Rise. The in-situ observations reveal integrated chlorophyll-a concentrations of up to 100 mg·m(-2), which suggests exceptionally high phytoplankton biomass within the Southern Ocean, thus making the seamount a regional phytoplankton hotspot.
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; oseanografi

Allometric relationships of ecologically important Antarctic and Arctic zooplankton and fish species - Schaafsma, Fokje L.; David, Carmen L.; Kohlbach, Doreen; Ehrlich, Julia; Castellani, Giulia; Lange, Benjamin A.; Vortkamp, Martina; Meijboom, André; Fortuna-Wünsch, Anna; Immerz, Antonia; Cantzler, Hannelore; Klasmeier, Apasiri; et al. (Polar Biology, 2022)
Allometric relationships between body properties of animals are useful for a wide variety of purposes, such as estimation of biomass, growth, population structure, bioenergetic modelling and carbon flux studies. This study summarizes allometric relationships of zooplankton and nekton species that play major roles in polar marine food webs. Measurements were performed on 639 individuals of 15 species sampled during three expeditions in the Southern Ocean (winter and summer) and 2374 individuals of 14 species sampled during three expeditions in the Arctic Ocean (spring and summer). The information provided by this study fills current knowledge gaps on relationships between length and wet/dry mass of understudied animals, such as various gelatinous zooplankton, and of animals from understudied seasons and maturity stages, for example, for the krill Thysanoessa macrura and larval Euphausia superba caught in winter. Comparisons show that there is intra-specific variation in length–mass relationships of several species depending on season, e.g. for the amphipod Themisto libellula. To investigate the potential use of generalized regression models, comparisons between sexes, maturity stages or age classes were performed and are discussed, such as for the several krill species and T. libellula. Regression model comparisons on age classes of the fish E. antarctica were inconclusive about their general use. Other allometric measurements performed on carapaces, eyes, heads, telsons, tails and otoliths provided models that proved to be useful for estimating length or mass in, e.g. diet studies. In some cases, the suitability of these models may depend on species or developmental stages.
Keywords: Sørishavet; biomasse; dyreplankton; fisker; marin biologi; marin økologi; polarområdene; zooplankton

Sea Ice CO2 Dynamics Across Seasons: Impact of Processes at the Interfaces - Van der Linden, Fanny; Tison, Jean-Louis; Champenois, Willy; Moreau, Sébastien; Carnat, Gauthier; Kotovitch, Marie; Fripiat, François; Deman, Florian; Roukaerts, Arnout; Dehairs, Frank; Wauthy, Sarah; Lourenço, Antonio; et al. (Journal of Geophysical Research: Oceans, 2020)
Winter to summer CO2 dynamics within landfast sea ice in McMurdo Sound (Antarctica) were investigated using bulk ice pCO2 measurements, air-snow-ice CO2 fluxes, dissolved inorganic carbon (DIC), total alkalinity (TA), and ikaite saturation state. Our results suggest depth-dependent biotic and abiotic controls that led us to discriminate the ice column in three layers. At the surface, winter pCO2 supersaturation drove CO2 release to the atmosphere while spring-summer pCO2 undersaturation led to CO2 uptake most of the time. CO2 fluxes showed a diel pattern superimposed upon this seasonal pattern which was potentially assigned to either ice skin freeze-thaw cycles or diel changes in net community production. In the ice interior, the pCO2 decrease across the season was driven by physical processes, mainly independent of the autotrophic and heterotrophic phases. Bottom sea ice was characterized by a massive biomass build-up counterintuitively associated with transient heterotrophic activity and nitrate plus nitrite accumulation. This inconsistency is likely related to the formation of a biofilm. This biofilm hosts both autotrophic and heterotrophic activities at the bottom of the ice during spring and may promote calcium carbonate precipitation.
Keywords: Sørishavet; biofilm; biomasse; geokjemi; karbon syklus; karbondioksid; landfast havis; landfast sjøis; oseanografi

Sea Ice Meltwater and Circumpolar Deep Water Drive Contrasting Productivity in Three Antarctic Polynyas - Moreau, Sebastien; Lannuzel, Delphine; Janssens, J.; Arroyo, Mar; Corkill, M; Cougnon, Eva; Genovese, C.; Legresy, Benoit; Lenton, Andrew; Puigcorbe, V.; Ratnarajah, L.; Rintoul, Steve; et al. (Journal of Geophysical Research: Oceans, 2019)
In the Southern Ocean, polynyas exhibit enhanced rates of primary productivity and represent large seasonal sinks for atmospheric CO2. Three contrasting east Antarctic polynyas were visited in late December to early January 2017: the Dalton, Mertz, and Ninnis polynyas. In the Mertz and Ninnis polynyas, phytoplankton biomass (average of 322 and 354 mg chlorophyll a (Chl a)/m2, respectively) and net community production (5.3 and 4.6 mol C/m2, respectively) were approximately 3 times those measured in the Dalton polynya (average of 122 mg Chl a/m2 and 1.8 mol C/m2). Phytoplankton communities also differed between the polynyas. Diatoms were thriving in the Mertz and Ninnis polynyas but not in the Dalton polynya, where Phaeocystis antarctica dominated. These strong regional differences were explored using physiological, biological, and physical parameters. The most likely drivers of the observed higher productivity in the Mertz and Ninnis were the relatively shallow inflow of iron-rich modified Circumpolar Deep Water onto the shelf as well as a very large sea ice meltwater contribution. The productivity contrast between the three polynyas could not be explained by (1) the input of glacial meltwater, (2) the presence of Ice Shelf Water, or (3) stratification of the mixed layer. Our results show that physical drivers regulate the productivity of polynyas, suggesting that the response of biological productivity and carbon export to future change will vary among polynyas.
Keywords: Sørishavet; biomasse; brehylle; fytoplankton; havis; isbrem; isshelf; marin biologi; oseanografi; polynja; sjøis

Feeding by Antarctic krill Euphausia superba in the West Antarctic Peninsula: differences between fjords and open waters - Cleary, Alison C; Durbin, Edward G; Casas, Maria C (Marine Ecology Progress Series, 2018)
Antarctic krill Euphausia superba are key components of Antarctic ecosystems, serving as the major prey item for most of the megafauna in the region. Coastal fjords along the West Antarctic Peninsula have been identified as biological hotspots, areas in which high biomasses of both E. superba and their megafauna predators are consistently observed. We investigated feeding by E. superba in fjords and adjacent open waters of the West Antarctic Peninsula. Next generation sequencing of stomach contents from 174 krill indicated a diverse diet, with broad patterns consistent with previous understanding of E. superba feeding. Diatom sequence reads were frequent and abundant, indicating a largely diatom-based diet, while the occasional presence of high abundances of copepod sequence reads suggests carnivory supplemented the diet. Striking differences were observed between the stomach contents of krill collected in fjords and those of krill collected in adjacent open waters. Chaetoceros spp. diatoms made up 71% of the stomach contents sequences of krill collected in fjords, but less than 10% of the stomach contents sequences of krill collected in open waters. These differences could not be explained by differences in the surface water phytoplankton communities, as in both open waters and fjords Chaetoceros spp. made up less than 10% of the surface water sequence read assemblages. These feeding differences highlight the importance of taking into account regional differences in krill feeding when considering E. superba’s roles in Southern Ocean ecosystems, and suggest krill in fjords may make use of vertical structure in phytoplankton assemblages.
Keywords: Sørishavet; biomasse; fytoplankton; krill; marin biologi; oseanografi; zoologi; økosystemer

Net Community Production in the Southern Ocean: Insights From Comparing Atmospheric Potential Oxygen to Satellite Ocean Color Algorithms and Ocean Models - Nevison, Cynthia; Munro, David; Lovenduski, Nicole; Cassar, Nicolas; Keeling, Ralph; Krummel, Paul; Tjiputra, Jerry (Geophysical Research Letters, 2018)
The contribution of oceanic net community production (NCP) to the observed seasonal cycle in atmospheric potential oxygen (APO) is estimated at Cape Grim, Tasmania. The resulting APONCP signal is compared to satellite and ocean model-based estimates of POC export and NCP across the Southern Ocean. The satellite products underestimate the amplitude of the observed APONCP seasonal cycle by more than a factor of 2. Ocean models suggest two reasons for this underestimate: (1) Current satellite products substantially underestimate the magnitude of NCP in early spring. (2) Seasonal O2 outgassing is supported in large part by storage of carbon in DOC and living biomass. More DOC observations are needed to help evaluate this latter model prediction. Satellite products could be improved by developing seasonally dependent relationships between remote sensing chlorophyll data and in situ NCP, recognizing that the former is a measure of mass, the latter of flux.
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; karboneksport; marin biologi; oseanografi

Planktonic food web structure at SSTF and PF in the Indian sector of the Southern Ocean during austral summer 2011 - Pillai, H U K; Anilkumar, N; Achuthankutty, C T; Mendes, C R; Sabu, P; Jayalakshmi, K V; Devi, C R Asha; Dessai, Deepti; George, Jenson; Pavithran, Sini; Hari Devi, C K; Tripathy, S C; et al. (Polar Research, 2018)
This study aims to describe the planktonic food web structure with respect to phytoplankton biomass (chlorophyll a ) and prevailing environmental conditions at the South Subtropical Front (SSTF) and the Polar Front (PF) in the Indian sector of the Southern Ocean. Sampling was carried out at each front for 72 hrs, at 6-hr intervals, during the austral summer 2011. Considerable variations were observed in the hydrography between these two fronts. A strong temperature minimum layer was observed at the PF. Although the surface primary production and chlorophyll a values showed similar trends at both the fronts, the water column values of these parameters showed major disparities. The phytoplankton composition also revealed marked difference between the fronts. A deep chlorophyll maximum concordant with the upper limit of the temperature minimum layer was prominent at the PF. The microzooplankton abundance at the SSTF was twice as high as at the PF. The mesozooplankton biovolume and population density also showed considerable variations between these fronts. Noticeable diel variations were observed in the surface mesozooplankton biovolumes at both the fronts and the copepod Pleuromamma gracilis showed active diel vertical migration at SSTF. Both the grazing and senescence indices showed significant variations between these fronts, suggesting a disparity in the ecological efficiency of the two regions. The variability observed in the plankton community structure with respect to the hydrography and the biological components measured suggests that a multivorous food web at the SSTF and a conventional food web at the PF prevailed during the period of study.
Keywords: Sørishavet; biomasse; fytoplankton; hydrografi; marin biologi; zooplankton; økosystemer

Increasing temperature may shift availability of euphausiid prey in the Southern Ocean - Richerson, Kate; Driscoll, Ryan; Mangel, Marc (Marine Ecology Progress Series, 2018)
Climate change is predicted to affect Southern Ocean biota in complex ways. Euphausiids play a crucial role in the trophodynamics of the ecosystem, and their status under future environmental scenarios is the subject of much concern. Thysanoessa macrura is the most widely distributed, numerically abundant, and ubiquitous euphausiid south of the Polar Front and may be an underappreciated prey species. T. macrura is eurythermic and may be better able to tolerate warming ocean temperatures in comparison to the more stenothermic Antarctic krill Euphausia superba. We use temperature-dependent growth models and biomass per recruit to investigate how the availability of this euphausiid to predators may change under a range of temperature scenarios. We contrast this with the availability of E. superba and find that, under some ranges of temperature change, increasing T. macrura growth may be able to partially compensate for decreasing E. superba growth in terms of biomass available for predators. However, in spite of its considerable biomass, other aspects of this species, such as its size and habitat, may limit its potential to replace E. superba in the diet of many predators. KEYWORDS: Thysanoessa macrura · Euphausia superba · Growth · Temperature · Climate change · Krill predators · Southern Ocean · Euphausiids · Modeling
Keywords: Sørishavet; biomasse; havoppvarming; klimaendringer; krill; marin biologi; marine økosystemer; miljøendringer; plankton

Remarkable structural resistance of a nanoflagellate-dominated plankton community to iron fertilization during the Southern Ocean experiment LOHAFEX - Schulz, Isabelle; Montresor, Marina; Klaas, Christine; Assmy, Philipp; Wolzenburg, Sina; Gauns, Mangesh; Sarkar, Amit; Thiele, Stefan; Wolf-Gladrow, Dieter; Naqvi, Wajih; Smetacek, Victor (Marine Ecology Progress Series, 2018)
The genesis of phytoplankton blooms and the fate of their biomass in iron-limited, high-nutrient-low-chlorophyll regions can be studied under natural conditions with ocean iron fertilization (OIF) experiments. The Indo-German OIF experiment LOHAFEX was carried out over 40 d in late summer 2009 within the cold core of a mesoscale eddy in the productive south-west Atlantic sector of the Southern Ocean. Silicate concentrations were very low, and phytoplankton biomass was dominated by autotrophic nanoflagellates (ANF) in the size range 3-10 µm. As in all previous OIF experiments, the phytoplankton responded to iron fertilization by increasing the maximum quantum yield (Fv/Fm) and cellular chlorophyll levels. Within 3 wk, chlorophyll levels tripled and ANF biomass doubled. With the exception of some diatoms and dinoflagellates, the biomass levels of all other groups of the phyto- and protozooplankton (heterotrophic nanoflagellates, dinoflagellates and ciliates) remained remarkably stable throughout the experiment both inside and outside the fertilized patch. We attribute the unusually high biomass attained and maintained by ANF to the absence of their grazers, the salps, and to constraints on protozooplankton grazers by heavy predation exerted by the large copepod stock. The resistance to change of the ecosystem structure over 38 d after fertilization, indicated by homogeneity at regional and temporal scales, suggests that it was locked into a stable, mature state that had evolved in the course of the seasonal cycle. The LOHAFEX bloom provides a case study of a resistant/robust dynamic equilibrium between auto- and heterotrophic ecosystem components resulting in low vertical flux both inside and outside the patch despite high biomass levels. KEYWORDS: Antarctic · Protists · Fe-limitation · Si-limitation · Ecology-biogeochemistry relationship · Carbon:chlorophyll ratios · Ecosystem stability
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; økologi; økosystemer

Spring phenology shapes the spatial foraging behavior of Antarctic petrels - Fauchald, Per; Tarroux, Arnaud; Tveraa, Torkild; Cherel, Yves; Ropert-Coudert, Yan; Kato, Akiko; Love, Oliver P; Varpe, Øystein; Descamps, Sébastien (Marine Ecology Progress Series, 2017)
In polar seas, the seasonal melting of ice triggers the development of an open-waterecosystem characterized by short-lived algal blooms, the grazing and development of zooplank-ton, and the influx of avian and mammalian predators. Spatial heterogeneity in the timing of icemelt generates temporal variability in the development of these events across the habitat, offeringa natural framework to assess how foraging marine predators respond to the spring phenology.We combined 4 yr of tracking data of Antarctic petrels Thalassoica antarcticawith synopticremote-sensing data on sea ice and chlorophyll ato test how the development of melting ice andprimary production drive Antarctic petrel foraging. Cross-correlation analyses of first-passagetime revealed that Antarctic petrels utilized foraging areas with a spatial scale of 300 km. Theseareas changed position or disappeared within 10 to 30 d and showed no spatial consistency amongyears. Generalized additive model (GAM) analyses suggested that the presence of foraging areaswas related to the time since ice melt. Antarctic petrels concentrated their search effort in meltingareas and in areas that had reached an age of 50 to 60 d from the date of ice melt. We found nosignificant relationship between search effort and chlorophyll aconcentration. We suggest thatthese foraging patterns were related to the vertical distribution and profitability of the main prey,the Antarctic krill Euphausia superba. Our study demonstrates that the annual ice melt in theSouthern Ocean shapes the development of a highly patchy and elusive food web, underscoringthe importance of flexible foraging strategies among top predators. KEY WORDS: Area-restricted search · Euphausia superba· Marginal ice zone · Phytoplanktonbiomass · Procellariiformes · Sea ice dynamics · Southern Ocean · Thalassoica antarctica
Keywords: Sørishavet; Weddellhavet; biologi; biomasse; fenologi; fytoplankton; fôring; havis; klima; petreller; sjøis; smelting; økosystemer

Algal biomass and pigments along a latitudinal gradient in Victoria Land lakes, East Antarctica - Borghini, Francesca; Colacevich, Andrea; Caruso, Tancredi; Bargagli, Roberto (Polar Research, 2016)
It is generally accepted that Antarctic terrestrial diversity decreases as latitude increases, but latitudinal patterns of several organisms are not always as clear as expected. The Victoria Land region is rich in lakes and ponds and spans 8 degrees of latitude that encompasses gradients in factors such as solar radiation, temperature, ice cover and day length. An understanding of the links between latitudinally driven environmental and biodiversity changes is essential to the understanding of the ecology and evolution of Antarctic biota and the formulation of hypotheses about likely future changes in biodiversity. As several studies have demonstrated that photosynthetic pigments are an excellent, although underused, tool for the study of lacustrine algal communities, the aim of the present study was to investigate variations in algal biomass and biodiversity across the latitudinal gradient of Victoria Land using sedimentary pigments. We test the hypothesis that the biodiversity of freshwater environments decreases as latitude increases. On the basis of our results, we propose using the number of sedimentary pigments as a proxy for algal diversity and the sum of chlorophyll a and bacteriochlorophyll a with their degradation derivatives as an index of biomass. Overall, our data show that biomass and diversity decrease as latitude increases but local environmental conditions, in particular, natural levels of eutrophy, can affect both productivity and diversity. Keywords: Biodiversity; photosynthetic pigments; proxy; continental Antarctica; sediments; biogeography.
Keywords: Antarktis; alger; biodiversitet; biogeografi; biomasse; ferskvann; fotosyntese; innsjø; sedimenter; økologi

Winter distribution and size structure of Antarctic krill Euphausia superba populations in-shore along the West Antarctic Peninsula - Cleary, Alison C; Durbin, Edward G; Casas, Maria C; Zhou, Meng (Marine Ecology Progress Series, 2016)
Antarctic krill Euphausia superba are a key component of food webs in the maritime West Antarctic Peninsula, and their life history is tied to the seasonal cycles of sea ice and primary production in the region. Previous work has shown a general in-shore migration of krill in winter in this region; however, the very near-shore has not often been sampled as part of these surveys. We investigated distribution, abundance, and size structure of krill in 3 fjordic bays along the peninsula, and in the adjacent Gerlache Strait area using vertically stratified MOCNESS net tows and ADCP acoustic biomass estimates. Krill abundance was high within bays, with net estimated densities exceeding 60 krill m-3, while acoustic estimates were an order of magnitude higher. Krill within bays were larger than krill in the Gerlache Strait. Within bays, krill aggregations were observed near the seafloor during the day with aggregations extending to the sediment interface, and exhibited diel vertical migration higher into the water column at night. We suggest these high winter krill abundances within fjords are indicative of an active seasonal migration by krill in the peninsula region. Potential drivers for such a migration include reduced advective losses and costs, and availability of sediment food resources within fjords. Seasonally near-shore krill may also affect stock and recruitment assessments and may have implications for managing the krill fishery in this area. KEYWORDS: Euphausiid · Abundance · Diel vertical migration · DVM · WAP · Fjord.
Keywords: Sørishavet; biomasse; hydrografi; krill; marin biologi; oseanografi; zooplankton

Resources for fish feed in future mariculture - Olsen, Yngvar (Aquaculture Environment Interactions, 2011)
There is a growing concern about the ability to produce enough nutritious food to feed the global human population in this century. Environmental conflicts and a limited freshwater supply constrain further developments in agriculture; global fisheries have levelled off, and aquaculture may have to play a more prominent role in supplying human food. Freshwater is important, but it is also a major challenge to cultivate the oceans in an environmentally, economically and energy-friendly way. To support this, a long-term vision must be to derive new sources of feed, primarily taken from outside the human food chain, and to move carnivore production to a lower trophic level. The main aim of this paper is to speculate on how feed supplies can be produced for an expanding aquaculture industry by and beyond 2050 and to establish a roadmap of the actions needed to achieve this. Resources from agriculture, fish meal and fish oil are the major components of pellet fish feeds. All cultured animals take advantage of a certain fraction of fish meal in the feed, and marine carnivores depend on a supply of marine lipids containing highly unsaturated fatty acids (HUFA, with ≥3 double bonds and ≥20 carbon chain length) in the feed. The availability of HUFA is likely the main constraint for developing carnivore aquaculture in the next decades. The availability of fish meal and oil will decrease, and the competition for plant products will increase. New harvested resources are herbivore zooplankton, such as Antarctic krill and red feed, and new produced resources are macroalgae, transgenic higher HUFA-producing plants and bacterial biomass. These products are to a limited extent components of the human food chain, and all these resources will help to move cultured carnivores to lower trophic levels and can thereby increase the production capacity and the sustainability of the production. Mariculture can only become as successful as agriculture in the coming century if carnivores can be produced at around Trophic Level 2, based mainly on plant resources. There is little potential for increasing the traditional fish meal food chain in aquaculture. KEYWORDS: Global aquaculture · Mariculture · Feed resources · Marine lipids · HUFA · Trophic level
Keywords: Sørishavet; alger; bakterier; biomasse; bioressurser; fiskeri; havbruksnæring; jordbruk; krill; marin biologi; marine planter; matproduksjon; oseanografi; zooplankton

Spring phytoplankton onset after the ice break-up and sea-ice signature (Adélie Land, East Antarctica) - Riaux-Gobin, Catherine; Poulin, Michel; Dieckmann, Gerhard; Labrune, Céline; Vétion, Gilles (Polar Research, 2011)
The phytoplankton onset following the spring ice break-up in Adélie Land, East Antarctica, was studied along a short transect, from 400 m off the continent to 5 km offshore, during the austral summer of 2002. Eight days after the ice break-up, some large colonial and solitary diatom cells, known to be associated with land-fast ice and present in downward fluxes, were unable to adapt in ice-free waters, while some other solitary and short-colony forming taxa (e.g., Fragilariopsis curta, F. cylindrus) did develop. Pelagic species were becoming more abundant offshore, replacing the typical sympagic (ice-associated) taxa. Archaeomonad cysts, usually associated with sea ice, were recorded in the surface waters nearshore. Rough weather restricted the data set, but we were able to confirm that some microalgae may be reliable sea-ice indicators and that seeding by sea ice only concerns a few taxa in this coastal area of East Antarctica. Keywords: Ice break-up; phytoplankton; sea-ice signature; East Antarctica
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; havis; oseanografi; sjøis

Tracing biomass burning aerosol from South America to Troll Research Station, Antarctica - Fiebig, Markus; Lunder, Chris René; Stohl, Andreas (Geophysical Research Letters, 2009)
The atmospheric observatory at the Norwegian Research Station Troll in Queen Maud Land, Antarctica, holds, since February 2007, the first all-year Antarctic atmospheric aerosol particle number size distribution measurements. These are colocated with measurements of the aerosol absorption and spectral scattering coefficients. In June 2007, this instrument set observed an aerosol whose properties were indicative of a biomass burning aerosol. These properties included two log-normal size distribution modes with median particle diameters of 0.105 μm and 0.36 μm, sharply falling off to smaller and larger sizes, and peaks in scattering and absorption coefficient. With backward plume calculations of the Lagrangian transport model FLEXPART and the MODIS fire activity product, a source-receptor relationship was established between biomass burning events in Central Brazil and the aerosol seen at Troll. This is the first direct evidence that the Antarctic continent is susceptible to emissions from as far north as Southern tropical latitudes.
Keywords: Dronning Maud Land; Troll forskningsstasjon; biomasse; klimatologi; meteorologi; utslipp

Metabolism and biomass vertical distribution of zooplankton in the Bransfield Strait during the austral summer of 2000 - Yebra, Lidia; Hernández-León, Santiago; Almeida, Carlos; Bécognée, Pierrick (Polar Research, 2009)
The vertical distribution (0–550 m) of zooplankton biomass, and indices of respiration (electron transfer system [ETS]) and structural growth (aminoacyltRNA synthetases activity [AARS]), were studied in waters off the Antarctic Peninsula during the austral summer of 2000. The dominant species were the copepod Metridia gerlachei and the euphausiid Euphausia superba. We observed a vertical krill/copepod substitution in the water column. The zooplankton biomass in the layer at a depth of 200–500 m was of the same magnitude as the biomass in the layer at a depth of 0–200 m, indicating that biomass in the mesopelagic zone is an important fraction of the total zooplankton in Antarctic waters. The metabolic rates of the zooplankton community were sustained by less than 0.5% of the primary production in the area, suggesting that microplankton or small copepods are the main food source. Neither food availability nor predation seemed to control mesozooplankton biomass. The wide time lag between the abundance peak of the dominant copepod (M. gerlachei) and the phytoplankton bloom is suggested to be the main explanation for the low summer zooplankton biomass observed in these waters.
Keywords: Sørishavet; biomasse; fytoplankton; hydrologi; krill; metabolisme; oseanografi; zooplankton

Comparison of the microalgal community within fast ice at two sites along the Ross Sea coast, Antarctica - Ryan, K.G.; Hegseth, E.N.; Martin, A.; Davy, S.K.; O'Toole, R.; Ralph, P.J.; McMinn, A.; Thorn, C.J. (Antarctic Science, 2006)
Diverse microbial communities survive within the sea ice matrix and are integral to the energy base of the Southern Ocean. Here we describe initial findings of a four season survey (between 1999–2004) of community structure and biomass of microalgae within the sea ice and in the underlying water column at Cape Evans and Cape Hallett, in the Ross Sea, Antarctica as part of the Latitudinal Gradient Project. At Cape Evans, bottom-ice chlorophyll a levels ranged from 4.4 to 173 mg Chl a m−2. Dominant species were Nitzschia stellata, N. lecointei, and Entomoneis kjellmanii, while the proportion of Berkeleya adeliensis increased steadily during spring. Despite being obtained later in the season, the Cape Hallett data show considerably lower standing stocks of chlorophyll ranging from 0.11 to 36.8 mg Chl a m−2. This difference was attributed to a strong current, which may have ablated much of the bottom ice biomass and provided biomass to the water below. This loss of algae from the bottom of the ice may explain why the ice community contributed only 2% of the standing stock in the total water column. Dominant species at Cape Hallett were Nitzschia stellata, Fragilariopsis curta and Cylindrotheca closterium. The low biomass at Cape Hallett and the prevalence of smaller-celled diatoms in the bottom ice community indicate that the ice here is more typical of pack ice than fast ice. Further data will allow us to quantify and model the extent to which ice-driven dynamics control the structure and function of the sea ice ecosystem and to assess its resilience to changing sea ice conditions.
Keywords: Rosshavet; Sørishavet; alger; biomasse; fytoplankton; marin biologi

Ice algae during EPOS, leg 1: assemblages, biomass, origin and nutrients - Syvertsen, Erik E; Kristiansen, Svein (Polar Biology, 1993)
Keywords: Sørishavet; Weddellhavet; alger; biomasse

Phytoplankton distribution in relation to sea ice, hydrography and nutrients in the northwestern Weddell Sea in early spring 1988 during EPOS - Bianchi, Franco; Boldrin, Alfredo; Cioce, F; Dieckmann, Gerhard Stephan; Kuosa, Harri; Larsson, A M; Nöthig, Eva-Maria; Sehlstedt, P I; Socal, Giorgio; Syvertsen, Erik E (Polar Biology, 1992)
Phytoplankton biomass and distribution of major phytoplankton groups were investigated in relation to sea ice conditions, hydrography and nutrients along three north-south transects in the north western Weddell Sea in early spring 1988 during the EPOS Study (European Polarstern Study), Leg 1. Three different zones along the transects could be distinguished: 1) the Open Water Zone (OWZ) from 58-degrees to 60-degrees-S with high chlorophyll a concentrations up to 3.5-mu-g l-1; 2) the Marginal Ice Zone (MIZ) from 60-degrees to about 62.5-degrees with chlorophyll a concentrations between 0.1 and 0.3-mu-g l-1, and 3) the closed pack-ice zone (CPI) from 62.5-degrees to 63.2-degrees-S with chlorophyll a concentrations below 0.1-mu-g l-1. Nutrient concentrations increased towards the south showing winter values under the closed pack-ice. Centric diatoms such as Thalassiosira gravida and Chaetoceros neglectum forming large colonies dominated the phytoplankton assemblage in terms of biomass in open water together with large, long chain forming, pennate diatoms, whereas small pennate diatoms such as Nitzschia spp., and nanoflagellates prevailed in ice covered areas. Fairly low concentrations of phytoplankton cells were encountered at the southernmost stations and many empty diatom frustules were found in the samples. The enhanced phytoplankton biomass in the Weddell-Scotia-Confluence area is achieved through sea ice melting in the frontal zone of two different water masses, the Weddell and the Scotia Sea surface waters.
Keywords: Sørishavet; Weddellhavet; biomasse; diatomeer; fytoplankton; havis; hydrografi; marin biologi; oseanografi

Phytoplankton-bacteria relationship in the Antarctic marine ecosystem - Billen, Gilles; Becquevort, Sylvie (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; bakterier; biomasse; fytoplankton; marin biologi; oseanografi; økofysiologi; økosystemer

Microbial autotrophic and heterotrophic eucaryotes in Antarctic waters: relationships between biomass and chlorophyll, adenosine triphosphate and particulate organic carbon - Hewes, Christopher D.; Sakshaug, Egil; Reid, Freda M. H.; Holm-Hansen, Osmund (Marine Ecology Progress Series, 1990)
Microscopical examination of near-surface eucaryotic microbial populations in circumcontinental waters of Antarctica indicated that nanoplankton (<20 μm diameter) dominated in regions with low chlorophyll concentrations (< 1 μg l⁻¹). About 30 % of the mean nanoplankton carbon consisted of heterotrophic flagellates. Heterotrophic microplankton carbon (> 20 μm diameter) was generally less significant. The variation in phytoplankton biomass was the result primarily of changes in cell density of pennate diatoms in the East Wind Drift, and of centric diatoms in the Weddell Sea and the Scotia Ridge region. Autotrophic and heterotrophic carbon as determined by microscopical analysis were compared with data for total particulate carbon, chlorophyll a, and adenosine triphosphate. Estimates for the C:chl ratio of autotrophs increased with decreasing concentrations of chlorophyll a, with mean values of 46 in bloom waters and 144 in 'blue water'. A C:ATP ratio for heterotrophic nanoplankton was estimated to be about 100, while that for heterotrophic microplankton may be lower. Algorithms, incorporating concentrations of chlorophyll a and ATP, are described which allow estimates of autotrophic and heterotrophic microbial biomass.
Keywords: Sørishavet; alger; biomasse; fytoplankton; marin biologi; oseanografi; plankton; zooplankton

Phytoplankton blooms in the vicinity of palmer station, Antarctica - Holm-Hansen, Osmund; Mitchell, Brian Gregory; Hewes, Christopher D; Karl, David Michael (Polar Biology, 1989)
Fifteen oceanographic stations were occupied in the vicinity of Anvers Island, Antarctica, in January of 1985 and 1987. All stations showed high phytoplankton biomass (4.0 to 30 μg chl-a/liter) which was either uniformly distributed in the upper mixed layer or showed a pronounced sub-surface maximum at 4–5 m depth. As phosphate was less than 0.02 μm and nitrate about 2.0 μm in surface waters, it appears that nutrient limitation of phytoplankton growth may be of importance during such blooms. This view is supported by chemical measurements of the particulate material which showed high chl-a/ATP ratios (about 7.7), as well as high POC/ATP ratios (about 700). Microscopical analysis revealed a dominance of large-celled diatoms and the near absence of heterotrophic protozoans. Size fractionation studies showed that the nanoplankton accounted for only 28% of the total phytoplankton biomass. When phytoplankton biomass reaches the levels found at these stations, it appears that the cells are light-limited and hence dark-adapted, which results in the high chl-a/ATP ratios and the low assimilation values (0.49–1.64) obtained in our studies. Under such conditions greater than 50% of the total phytoplankton biomass is found below the 1% light level.
Keywords: Sørishavet; biomasse; fytoplankton; oseanografi